MORBIMORTALITY STUDY PROFILE AMONGST ELDERLY - Juliana Balbinot Reis Girondi; Simone Cristine dos Santos Nothaft; Silvia Maria Azevedo dos Santos; Fernanda de Oliveira; Luciara Fabiane Sebold; Silvana Silveira Kempfer (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976926704 Aim: to identify the morbimortality profile amongst elderly between 1996 and 2007 in the States of Santa Catarina and Bahia - Brazil. Method: a quantitative, ecological time-series study. Data were collected during the months of September to November 2010, directly accessed from the Information System on Mortality and Hospital Information System from the Ministry of Health. Data were analysed by descriptive statistic, by proportion of diseases temporarily identified and by percentage comparison between both States under study. Results: despite predominance of chronic degenerative diseases, deaths by ill-defined causes and both infectious and parasitic diseases are still proportionally high. Conclusion: regarding morbidity, there are small differences between groups of causes. As to mortality, circulatory system and neoplasms diseases prevail in Santa Catarina; abnormal symptoms, signs and findings during clinical and lab exams, followed by circulatory system diseases prevail in Bahia.